Role of Episamarcandin in Promoting the Apoptosis of Human Colon Cancer HCT116 Cells through the PI3K-Akt Signaling Pathway - Haiying Zhang (Hindawi Limited, 2021)
This study identifies the active ingredients of Ferula sinkiangensis and investigates the role and mechanism of episamarcandin in colon cancer cells. The silica gel column chromatography was utilized to separate the chemical components of Ferula sinkiangensis. Sephadex LH-20 and semipreparative HPLC were adopted for further separation and purification. The compound episamarcandin showed good anticolon cancer activity among the 13 monomeric compounds obtained. Its effects on the apoptosis, cell cycle, and invasion and migration of colon cancer HCT 116 cells and PI3K-Akt signaling pathway were further investigated. The results showed that, similar to positive control cisplatin, episamarcandin inhibited the proliferation, promoted the apoptosis, arrested cells at G0/G1 phase, and suppressed migration and invasion of HCT 116 cells. A large number of apoptotic HCT 116 cells were observed under a transmission electron microscope. Fluorescence real-time quantitative PCR and western blot analysis showed that episamarcandin increased the expression of PTEN, p53, and Bax and decreased the expression of P-Akt, Akt, mTOR, Bcl-xl, and Bcl-2. Conclusively, episamarcandin may inhibit cell proliferation, migration, and invasion and promote the apoptosis of human colon cancer HCT 116 cells possibly through the PI3K-Akt signaling pathway.